(untitled) (Revista do Serviço Público, 2026)
This case study employs an intersectional lens to find the mechanisms influencing black women’s experiences regarding leadership positions in the executive branch of Minas Gerais. It was employed a qualitative analysis by conducting ten interviews with black women, who either formerly held or occupied leadership roles in the executive branch when interviewed. Additionally, this study is framed within the scholarship on political representation, which explores the presence of minority groups in the political sphere, connecting their participation with policy outcomes. The central argument is that these women’s identity as black female leaders results in their unique political experiences and places them in specific roles in securing political representation for this group. Several mechanisms emerged: racial identity, misogynoir, family, personality traits and the presence of critical allies. This indicates that black women’s political reality is unique, considering they suffer from combined oppressions and that misogynoir affects only this group. Lastly, this research adds to the existing scholarship by addressing not only this group’s barriers but also mechanisms enabling this group to tackle oppression and achieve leadership positions.